2013
DOI: 10.1017/s0007114513003371
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tissue distribution and concentration of β-cryptoxanthin in response to varying amounts of dietary β-cryptoxanthin in the Mongolian gerbil

Abstract: There is a general lack of knowledge regarding the absorption and tissue storage of the provitamin A carotenoid b-cryptoxanthin. The present study investigated the whole-body tissue distribution of b-cryptoxanthin in an appropriate small animal model, the Mongolian gerbil (Meriones unguiculatus), for human provitamin A carotenoid metabolism. After 5 d of carotenoid depletion, five gerbils were euthanised for baseline measurements. The remaining gerbils were placed in three weight-matched treatment groups (n 8)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Moreover, these tropical varieties contain more β-cryptoxanthin and less β-carotene, and the emphasis was to enhance the β-carotene, which provides two vitamin A molecules per carotenoid molecule. 2 However, animal studies have shown that β-cryptoxanthin is absorbed and stored in many tissues 16 and it maintains the vitamin A status of gerbils as efficiently or better than β-carotene. 17 Most of the yellow maize grown and consumed throughout the world has less than 2.0 μg/g DW of provitamin A carotenoids in kernels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, these tropical varieties contain more β-cryptoxanthin and less β-carotene, and the emphasis was to enhance the β-carotene, which provides two vitamin A molecules per carotenoid molecule. 2 However, animal studies have shown that β-cryptoxanthin is absorbed and stored in many tissues 16 and it maintains the vitamin A status of gerbils as efficiently or better than β-carotene. 17 Most of the yellow maize grown and consumed throughout the world has less than 2.0 μg/g DW of provitamin A carotenoids in kernels.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…folate, β-cryptoxanthin) may be also absorbed across the . The presence of several unidentified peaks is also detected (see text) (t-βC All-trans-β-carotene, cis-βC cis-β-carotene) colon [7,14] where they or their metabolites may exert antitumor effects [3,12]. In order to assess the presence and the relative proportions of dietary components at target tissues, the collection device evaluated was found to be easy to use and representative of a faeces sample making it suitable for studying fat-soluble bioactive compounds available at the colon.…”
Section: Discussionmentioning
confidence: 96%
“…While bioavailability of vitamin A and E may be relatively high, bioaccessibility of carotenoids from vegetables is low and several studies indicate that more than 70 % of the carotenoids may remain in the final digesta [1,[5][6][7]. Then, poorly bioavailable micronutrients like carotenoids may reach significant concentrations in the gastrointestinal tract where they may exert biological actions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Triacylglycerol-rich plasma carotenoids and retinoids were separated with an YMC column (Carotenoid S-3 μm, 50×2.1 mm) using an isocratic mobile phase: 70:20:10 (v/v/v) acetonitrile-dichloromethane-methanol, as previously described [30,31]. Triacylglycerol plasma extract size was 100 μL, of which 20 μL was injected onto the column.…”
Section: Methodsmentioning
confidence: 99%